ASSESSING DIGITAL READINESS OF BORDER SMES: A COMPARATIVE STUDY BETWEEN BENGKALIS AND MUAR - Halim Dwi Putra; Samshul Amry Bin Abdul Latif; Aswandi Aswandi (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to assess and compare the digital readiness of Small and Medium Enterprises (SMEs) located in the border regions of Bengkalis, Indonesia, and Muar, Malaysia, as they confront the accelerating demands of Industry 4.0. The objectives are to identify the level of technological adoption, evaluate the enabling and inhibiting factors for digital transformation, and determine the role of local ecosystems in supporting SME digitalization in these two geographically connected but administratively distinct areas. Despite growing interest in digital economy initiatives across Southeast Asia, border-area SMEs remain under-researched, especially in terms of their preparedness for digital competition and cross-border market integration. A quantitative comparative approach was employed using structured questionnaires distributed to 100 SMEs, equally divided between Bengkalis and Muar. The data was analyzed using descriptive statistics, t-tests, and correlation analyses to highlight readiness gaps and similarities across key dimensions such as infrastructure, skills, organizational strategy, and external support systems. This research is significant for policymakers, development agencies, and academic communities interested in narrowing the digital divide and strengthening cross-border SME ecosystems. The findings are expected to contribute to the formulation of targeted interventions, particularly through Penta-helix collaboration involving government, academia, private sector, media, and communities, to boost SME competitiveness and sustainability in border regions. The study underscores the need for localized digital strategies that recognize socio-economic and cultural differences across national boundaries.